2‐nm‐Thick Indium Oxide Featuring High Mobility. Issue 9 (25th February 2023) - Nguyen, Chung Kim; Mazumder, Aishani; Mayes, Edwin LH; Krishnamurthi, Vaishnavi; Zavabeti, Ali; Murdoch, Billy J.; Guo, Xiangyang; Aukarasereenont, Patjaree; Dubey, Aditya; Jannat, Azmira; Wei, Xiaotian; Truong, Vi Khanh; et al.
Abstract: Thin film transistors (TFTs) are key components for the fabrication of electronic and optoelectronic devices, resulting in a push for the wider exploration of semiconducting materials and cost‐effective synthesis processes. In this report, a simple approach is proposed to achieve 2‐nm‐thick indium oxide nanosheets from liquid metal surfaces by employing a squeeze printing technique and thermal annealing at 250 °C in air. The resulting materials exhibit a high degree of transparency (>99 %) and an excellent electron mobility of ≈96 cm 2 V −1 s −1, surpassing that of pristine printed 2D In2 O3 and many other reported 2D semiconductors. UV‐detectors based on annealed 2D In2 O3 also benefit from this process step, with the photoresponsivity reaching 5.2 × 10 4 and 9.4 × 10 3 A W −1  at the wavelengths of 285 and 365 nm, respectively. These values are an order of magnitude higher than for as‐synthesized 2D In2 O3 . Utilizing transmission electron microscopy with in situ annealing, it is demonstrated that the improvement in device performances is due to nanostructural changes within the oxide layers during annealing process. This work highlights a facile and ambient air compatible method for fabricating high‐quality semiconducting oxides, which will find application in emerging transparent electronics and optoelectronics. Abstract : 2‐nm‐thick indium oxide nanosheets with high electron mobility have been synthesized utilizing a liquid metal printing technique and thermal annealing in air. Transmission electron microscopy with in situ annealing reveals that the improvement in device performances is due to nanostructural changes during annealing process. This work highlights a facile and ambient air compatible method for fabricating high‐quality semiconductors, which find application in emerging electronics and optoelectronics.